Tradisi Unik Dalam Pelaksanaan Pujawali Pura Desa Adat Gunung Luwih Kecamatan Sukadasa Buleleng - Sriasih, Ni Wayan; Mastiningsih, Ni Nyoman (Prabha Vidya, 2024)
This research aims to analyze the implementation of the Maboros tradition of a series of Pujawali by the people of Gunung Luwih Traditional Village as well as the stages and implications for the social value of communication in society. The method used in this research is a qualitative descriptive method. Data collection was carried out using observation techniques, interviews, and document recording techniques. Data were analyzed using descriptive and inductive techniques. The research results show that the meaning of the Maboros traditional philosophy is closely related to the piodalan ceremony at the village temple, where the meat of animals hunted in the forest can be processed into the contents of the kawas in a series of piodalan ceremonies at the village temple. The Maboros tradition is a series of piodalan ceremonies at the Gunung Luwih Traditional Village Temple which functions as a cultural function, social function and service function. The implication contained in the Maboros tradition is that there is sacredness and uniqueness when carrying out the ngider bhuwana ceremony and it has a dresta character. The meanings contained are religious meaning, cultural meaning, and educational meaning. The Maboros tradition aims to confine people's dirty thoughts so that they do not cause problems during the Pujawali Ceremony at the Village Temple.